Banking Mūrabaḥah: in the light of Qur’anic teachings - Dr. Hafsa Abbasi,; Dr Khadija Aziz,; Haleema Sadia, (Al Manhal Research Journal, 2023)
Mūrabaḥah lil-’Amir bi al-shira’i (Mūrabaḥah to the purchase orderer) is one of the most important mode of finance in Islamic Banking. It is serving as most extensively used tool in that industry. Its permissibility is being approved by AAIOFI and Majma‘ al-fiqh al-Islāmī. Yet it is being highly criticized by the majority of the scholars for having many doubtful elements in it. Mūrabaḥah is named as Mūrabaḥah to the purchase orderer because it is different from original and classical Mūrabaḥah sale. This new type of Mūrabaḥah sale includes prior agreement between client and the bank. This agreement is binding between the parties. Secondly, payment in Mūrabaḥah to the purchase orderer is deferred. It is called as bay‘ al-mū᾽ajal (deferred sale) in Islamic Finance. Thirdly, the bank appoints the client as its agent for purchasing commodities. Above mentioned elements and many more are not present in classical Mūrabaḥah sale. Thus, these issues need to be scrutinized from the Sharī‘ah perspective. This article revolves around these issues and debate of advocates and opponents of Mūrabaḥah to the purchase orderer. It also discusses the method being followed by Islamic Banks for practicing Mūrabaḥah. It further covers the origin and expansion of Mūrabaḥah to the purchase orderer. Who gave the idea of Banking Mūrabaḥah first time and on the base of what arguments? Banking Mūrabaḥah which is named as Mūrabaḥah lil-’Amir bi al-shira’i (Mūrabaḥah to the Purchase Orderer) is one of the most important mode of Finance in Islamic Banking. It is serving as the back bone of this industry. It would not be untrue if said that Islamic Banking would not be able to survive without Mūrabaḥah to the Purchase Orderer (MPO) and Ijārah. MPO is permitted by AAIOFI and Majma‘ al-Fiqh al-Islamī. This type of transaction has gained a very high rate of popularity. Therefore, it is very important to scrutinize the details of Mūrabaḥah Mode of Finance. MPO is stated to be a lawful and legitimate contract in Sharī‘ah by the institutions who have legalized it. But there are certain issues in it, which need to be pondered over. For example it was stated by Mufi Taqi Usmani and his co-workers to be the transitory step for Islamic Banking and never to serve as a permanent mode of Finance. Mufti Taqi Usmani states in his book about Mūrabaḥah: “In Islamic Banks this Mode (Mūrabaḥah) is being practiced excessively, but it is a very sensitive mode. Little carelessness can mix it up with Ribā based system. Nowadays, it is practiced in Banks without understanding its reality and without giving due care to its conditions. As a result lots problems are being created in this mode”. Still Mūrabaḥah is serving to be the most excessively used product of Islamic Banks. This article serves the purpose of highlighting the due care and diligence that has been maintained while practicing MPO. It revolves around regularities and irregularities of Banking Mūrabaḥah. First of all this article introduces the concept of Mūrabaḥah. Then its legality from Qur’an is given. Then this article covers the issues regarding Mūrabaḥah one after the other. Afterwards the method employed in Islamic Banking for the execution of Mūrabaḥah mode of Finance is covered. In the end it has been discussed that from where and how the idea of Banking Mūrabaḥah started.